The Influence of Production Factors and Dummy Partnerships on Broiler Poultry Production - Nurlela Machmuddin; Intani Dewi; Rayhana Jafar; Dira Asri Pramita (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Livestock activities are animal cultivation activities to obtain profits, one of which is obtained through increasing production. This research aims to analyze the influence of production factors, namely land size, capital, chicken seeds or DOC, feed, medicines, labor, cost of electricity, and partnership patterns, on broiler poultry production. The method used in the research is the linear regression analysis method using the Douglas production function. This study was conducted in North Tarakan District, Tarakan City, North Kalimantan. The research respondents were 30 broiler poultry breeders selected using a quota sampling technique consisting of independent and partner chicken breeders. The analysis results are as follows: 1) production factors that significantly affect broiler poultry production are chicken seeds (DOC) and feed. Meanwhile, production factors such as cage area, capital, labor, and electricity do not significantly influence broiler poultry production. 2) Dummy partnership patterns do not significantly affect broiler poultry production. However, in this case, study, the advantage that breeders get by partnering with plasma companies is that breeders get convenience in providing seeds (DOC), feed, medicines, and certainty of marketing by partners. Breeders get material and counseling for administering vaccines, disease prevention techniques, and medicines from partners. Stated that providing training and extension services has the potential to increase chicken productivity. While the disadvantage is possible losses from entering into a partnership, including that chicken breeders are not free to sell their production to other places if the price of chicken rises.